2014
DOI: 10.5539/gjhs.v6n5p196
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Patient Satisfaction of the Quality of Health Care Provided by Outpatient Services of an Oncology Hospital

Abstract: Aim:The purpose of this research is to investigate the patient’s satisfaction (patient’s satisfaction) with medical services provided in Outpatients’ Departments of a Greek Anti-Cancer Hospital in morning and afternoon clinics. The assessment of patients and identification of factors that contribute to their satisfaction will highlight the organizational and operational problems of outpatient department and assist in finding solutions to upgrade the quality of services provided.Material and Methodology:For the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 17 publications
(16 reference statements)
4
33
0
2
Order By: Relevance
“…Paying attention to the patient's symptoms as well as the physician's interest in the patient's medical problems are other very important factors for patient satisfaction. These results are consistent with previous studies conducted in dermatology and other specialties that showed that overall satisfaction is significantly influenced by the ability of the physician to focus on the patient's health and to give them explanations. Patients aged 50 years and older, who represent a significant portion of patients consulting a dermatologist, were also the most satisfied , which is a result found in various studies of satisfaction among outpatient and hospitalized patients.…”
Section: Discussionsupporting
confidence: 92%
“…Paying attention to the patient's symptoms as well as the physician's interest in the patient's medical problems are other very important factors for patient satisfaction. These results are consistent with previous studies conducted in dermatology and other specialties that showed that overall satisfaction is significantly influenced by the ability of the physician to focus on the patient's health and to give them explanations. Patients aged 50 years and older, who represent a significant portion of patients consulting a dermatologist, were also the most satisfied , which is a result found in various studies of satisfaction among outpatient and hospitalized patients.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, care quality was assessed using patient‐centred quality, individualised care and trust in nurses' instruments and we did not find any associations, between gender, education levels and assessments of care quality attributes within the age‐related subgroups,. This finding supports some earlier findings (Pini et al., ) but contradicts many others (e.g., Arraras et al., ; Ejaz et al., ; John et al., ; Wessels et al., ). Previous studies have suggested that perceived health status is associated with patients' assessments of quality care attributes (Brennan et al., ; Nguyen et al., ; Tremblay et al., ) and age (Browall et al., ; John et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…Patients' assessments of quality‐of‐care attributes in relation to their health status are rarer than studies on age and education levels. In one study, cancer patients' satisfaction was not associated with the perceived health status (Pini et al., ). In a second study, patients with good self‐assessed health status were more likely to report a positive overall experience with cancer services responsiveness (OR = 1.64, [1.28–2.10]) than those with poor self‐assessed health status (Tremblay et al., ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Th e research revealed that there was little consistency in the eff ect of age on satisfaction with care 10 . Pini et al 16 found no statistically signifi cant relationship of overall satisfaction with demographics and other factors, although grading of services seemed to be aff ected by the patient health status, education and sex. Patient satisfaction was predicted by younger age, female gender, and greater attention to how they were coping with their illness 17 .…”
Section: Sociodemographic and Hospital-related Featuresmentioning
confidence: 97%